BASIC REQUIREMENTS FOR THE DEVELOPMENT OF TOURISM INBULGARIA - Stanev, Georgi (E-Journal VFU, 2024)
: Serving tourists who have visited various destinations on the territory of the country requires the efforts and professional attitude of many specialists in the field. Tourists visit not only places of accommodation and food, but also other tourist sites. The adoption of functioning regulations is among the priorities of many state institutions. Their activity and the subsequent effectiveness of the decisions are essential for the quality provision of the tourist service and satisfying the wishes of the customers. In this regard, this material draws attention to the main regulatory requirements regarding leading state bodies that are relevant at the national and territorial level for the development of tourism.